Role of Defeat Sense in the Quality of the Marital Relationship among Infertile Women with the Mediating Role of Spiritual Experiences - Seyedeh Mohadeseh Rezaei; Seyed Mahmood Mosavinezhad; Elaheh Ayoobi; Ali Tayaranirad (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: Infertility is a multifaceted problem that can cause major disorders with emotional, social, and psychological consequences, such as reduced quality of marital relationship. Therefore, this study aimed to investigate the role of defeat sense in the quality of marital relationships among infertile women with the mediating role of spiritual experiences. Methods: This descriptive-correlational study was conducted based on a structural equation modeling method. The statistical population included all infertile females referring to the Royesh Infertility Center, Birjand, Iran, in spring 2020. The samples (n=120) were selected using the convenience sampling method. The participants completed the questionnaires, including the Defeat Scale (Gilbert and Allen, 1998), Daily Spiritual Experience Scale (Underwood and Teresi, 2002), and the Golombok Rust Inventory of Marital State (Rust et al., 1986). The collected data were analyzed in SPSS software (version 22) and PLS software (version 3). Results: The results showed that the defeat sense had a negative and significant effect on spiritual experiences (β=-0.663; P<0.01) and a positive and significant effect on the quality of marital relationship (β=0.679; P<0.01). It was also revealed that the effect of spiritual experiences on the quality of marital relationships was negative and significant (β=-0.537; P<0.01). The indirect path between defeat sense and the quality of marital relationship was significant through the mediating role of spiritual experiences (β=0.356; P<0.01). The index of goodness of fit= 0.443 indicated the general fitness of the study model. Conclusion: Based on the findings, in counseling infertile women, it is necessary to consider the role of positive and protective factors, such as spiritual experiences and appropriate support be provided in defining the defeat to improve the quality of the marital relationship among infertile women.